Predicting resolution of hypoglycemia with and without dextrose infusion in newborn infant of gestational diabetic mothers - Ibrahim, Mohammed; Hou, Wei; Decristofaro, Joseph; Maduekwe, Echezona T. (Frontiers in Pediatrics, 2022)
Introduction: Neonatal hypoglycemia (NH) may lead to significant neurological impairment if left untreated. Infants of gestational diabetic mothers (IGDM) are at increased risk of early NH and need to be screened. However, it is challenging to predict management with or without intravenous dextrose once hypoglycemia is identified. We evaluated the association between hypoglycemia risk scores at 1-hour of life and the need for intravenous dextrose for hypoglycemia resolution in IGDM. Methods: This was a retrospective cohort study of IGDM born at a gestational age ≥35 weeks from January 2015 to December 2017. NH was the disease of interest. The outcomes were the association of hypoglycemia risk score (HRS) with and without intravenous dextrose for hypoglycemia resolution. Each infant’s hypoglycemia risk score (HRS) was calculated using data extracted from the maternal and neonatal electronic medical records. Resolution of hypoglycemia with and without intravenous dextrose was compared between the low HRS (0-1) group and the high HRS (2-5) group. Results: Sixty-five infants were included in the study with a mean gestational age of 38.2±1 weeks for low HRS and 38.0±2 weeks for high HRS. While more children with high HRS were delivered by cesarean section (p = 0.04), hypoglycemia resolved more frequently without intravenous dextrose in infants with low HRS (p = 0.03). Conclusion: IGDM is at increased risk of NH. The resolution of hypoglycemia without dextrose infusion is frequently associated with low HRS at 1-hour of life. Early identification using HRS of IGDM whose hypoglycemia will resolve with or without intravenous dextrose may help clinicians triage newborns to either stay in the nursery or transfer for more invasive care.